Miniaturised Optical Fibre Sensor for Dew Detection Inside Organ Pipes. (28th August 2008) - Baldini, Francesco; Falciai, Riccardo; Mencaglia, Andrea Azelio; Senesi, Folco; Camuffo, Dario; della Valle, Antonio; Bergsten, Carl Johan
Abstract : A new optical sensor for the continuous monitoring of the dew formation inside organ pipes was designed. This aspect is particularly critical for the conservation of organs in unheated churches since the dew formation or the condensation on the pipe surfaces can contribute to many kinds of physical and chemical disruptive mechanisms. The working principle is based on the change in the reflectivity which is observed on the surface of the fibre tip, when a water layer is formed on its distal end. Intensity changes of the order of 35% were measured, following the formation of the water layer on the distal end of a 400/430 μ m optical fibre. Long-term tests carried out placing the fibre tip inside the base of an in-house-made metallic foot of an organ pipe located in an external environment revealed the consistency of the proposed system.